On the role of plant mitochondrial metabolism and its impact on photosynthesis in both optimal and sub-optimal growth conditions - Araújo, Wagner L.; Nunes-Nesi, Adriano; Fernie, Alisdair R. (Photosynthesis Research, 2014)
Given that the pathways of photosynthesis and respiration catalyze partially opposing processes, it follows that their relative activities must be carefully regulated within plant cells. Recent evidence has shown that the components of the mitochondrial electron transport chain are essential for the proper maintenance of intracellular redox gradients, to allow considerable rates of photorespiration and in turn efficient photosynthesis. Thus considerable advances have been made in understanding the interaction between respiration and photosynthesis during the last decades and the potential mechanisms linking mitochondrial function and photosynthetic efficiency will be reviewed. Despite the fact that manipulation of various steps of mitochondrial metabolism has been demonstrated to alter photosynthesis under optimal growth conditions, it is likely that these changes will, by and large, not be maintained under sub-optimal situations. Therefore producing plants to meet this aim remains a critical challenge. It is clear, however, that although there have been a range of studies analysing changes in respiratory and photosynthetic rates in response to light, temperature and CO2, our knowledge of the environmental impact on these processes and its linkage still remains fragmented. We will also discuss the metabolic changes associated to plant respiration and photosynthesis as important components of the survival strategy as they considerably extend the period that a plant can withstand to a stress situation.
Keywords: Abiotic and biotic stress; Carbon nitrogen balance; Optimal and sub-optimal growth conditions; Plant respiration; Photorespiration; Photosynthesis; Stress tolerance